View of Santa Clara Valley in spring - Gordon, John C., 1887-1967 (photographer) :::Creator::::::::::::
Panoramic landscape of orchards, water towers, houses, and barns spread across the Santa Clara Valley. In bottom of the photograph a road traverses the entire length of the panorama and turns sharply to the left on the far right side of the photograph. One of the most notable features of this photograph is the frequency and distribution of water towers among the orchards.